1999
DOI: 10.1021/ed076p114
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Continuous Instructional Development on Graduate and Undergraduate Students

Abstract: Attention to teaching and learning issues on a weekly basis appears to have been helpful in developing graduate students' potential as effective instructors and was well received by a majority of graduate instructors. Results of student evaluations indicate that graduate instructors in the trial group were rated more favorably than those in the comparison group in the areas of being prepared, providing lucid explanations, being effective at helping students learn to think, and overall performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…Brauchle and Jerich (1998) concluded that after an instructional development initiative for teaching assistants, the treatment group's student ratings (obtained from 106 students of seven experimental assistants) were statistically significantly higher than the control group's (obtained from 140 students of six control assistants; p < .01). In a study by Nurrenbern, Mickiewicz, and Francisco (1999), most of the items in the student questionnaire revealed no significant differences between the experimental group ( n = 1,239 students) and the control group ( n = 846). In Finkelstein's study (1995), a student survey indicated that students perceived an increase in number and quality of interactions from pre‐test to post‐test.…”
Section: Impact Of Instructional Development In Higher Education On Smentioning
confidence: 89%
“…Brauchle and Jerich (1998) concluded that after an instructional development initiative for teaching assistants, the treatment group's student ratings (obtained from 106 students of seven experimental assistants) were statistically significantly higher than the control group's (obtained from 140 students of six control assistants; p < .01). In a study by Nurrenbern, Mickiewicz, and Francisco (1999), most of the items in the student questionnaire revealed no significant differences between the experimental group ( n = 1,239 students) and the control group ( n = 846). In Finkelstein's study (1995), a student survey indicated that students perceived an increase in number and quality of interactions from pre‐test to post‐test.…”
Section: Impact Of Instructional Development In Higher Education On Smentioning
confidence: 89%
“…Reviewing the literature as a whole provides a starting point for better understanding TA training for inquiry-based laboratories. Weekly TA meetings are recommended in order to address the practical course details (Nurrenbern et al, 1999;Roehrig et al, 2003;Sandi-Urena et al, 2011). Shannon et al, 1998;Hammrich, 2001;Roehrig et al, 2003;Luft et al, 2004;Cho et al, 2010;Marbach-Ad et al, 2012;Kendall and Schussler, 2013).…”
Section: Ta Support In Laboratory Instructionmentioning
confidence: 99%
“…Discussing the practical details include: procedures, grading, content, problems/issues, responsibilities, and safety (e.g. Nurrenbern et al, 1999). Weekly TA meetings are recommended in order to address the practical course details (Nurrenbern et al, 1999;Roehrig et al, 2003;Sandi-Urena et al, 2011).…”
Section: Ta Support In Laboratory Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training can cover a variety of topics, including teacher readiness, teaching strategies, classroom management, and pedagogy. Training GTAs is essential for many reasons, including reducing classroom anxiety, increasing leadership capabilities, and increasing confidence and readiness both in the classroom and in research (Nurrenbern et al, 1999;Roach, 2003). Courses that cover basic teaching skills combined with GTAs' intuition, motivation, and general aptitude for teaching give graduate students an advantage as they move forward in their academic careers (Kenney, 2007).…”
mentioning
confidence: 99%